Building Social Capital in Micro Environment: The Family, Attachment Theory and Socialization - Ozmete , Emine (Nurture, 2011)
Social capital is an instantiated informal norm that promotes cooperation between two or more individuals. The understanding of social capital can provide valuable insights into the social network and links that individuals and communities have, and importantly how these networks and links can be utilized to contribute to positive outcomes for the individual and the community life. In this way the explaining of social capital may enlarge our understanding of how individuals can work cooperatively to achieve shared goals and to deal with difficulties within environment productively. In this period, families as micro environment create norms and social ties for their members. Bowlby’s “Attachment Theory” strongly suggests a positive domino effect of trusting relationships spreading out from the family and into wider circles of life. Individuals who see from their parents volunteering and supportive behaviors in childhood period, they are in more likely engage those behaviors for communities in adulthood-it has called as socialization of an individual-. Also this socialization process contributes to wider social networks. The study is a literature review deeply. It aims to investigate about building social capital in family as micro environment and, effect of attachment styles and socialization process for members in family life on their social capital.